LIMD1 phosphorylation in mitosis is required for mitotic progression and its tumor‐suppressing activity. (16th January 2019) - Zhou, Jiuli; Zhang, Lin; Zhou, Wei; Chen, Yuanhong; Cheng, Yufeng; Dong, Jixin
Abstract : LIM domains containing 1 (LIMD1) is a member of the Zyxin family proteins and functions as a tumor suppressor in lung cancer. LIMD1 has been shown to regulate Hippo‐YAP signaling activity. Here, we report a novel regulatory mechanism for LIMD1. We found that cyclin‐dependent kinase 1 (CDK1) and c‐Jun NH2‐terminal kinases 1/2 (JNK1/2) phosphorylate LIMD1 in vitro and in cells during anti‐tubulin drug‐induced mitotic arrest. Phosphorylation also occurs during normal mitosis. S272, S277, S421, and S424 were identified as the main phosphorylation sites in LIMD1. Deletion of LIMD1 resulted in a shortened mitotic cell cycle and phosphorylation of LIMD1 is required for proper mitotic progression. We further showed that the phosphorylation‐deficient mutant LIMD1‐4A is less active in suppressing cell proliferation, anchorage‐independent growth, cell migration, and invasion in lung cancer cells. Together, our findings suggest that LIMD1 is a key regulator of mitotic progression, and that dysregulation of LIMD1 contributes to tumorigenesis. Abstract : LIMD1 is a scaffold/adaptor protein that plays a role in a range of cellular processes and has been shown to act as a tumor suppressor in lung cancer. Here, we demonstrate that CDK1 and JNK1/2 phosphorylate LIMD1 in vitro and in cells during drug‐induced mitotic arrest. Phosphorylation occurs at multiple sites on LIMD1 and is required for proper mitotic progression. Moreover, a phosphorylation‐deficient mutant of LIMD1 is less active in suppressing lung cancer cell growth.